Typhoid Mary [videorecording (DVD)] : the most dangerous woman in America - Leavitt, Judith Walzer (WGBH Boston Video, 2005)
In 1906 in America it was first discovered that humans could transmit typhoid fever. This is a dramatization of the outbreak and a profile of Irish cook Mary Mallon, known as 'Typhoid Mary'. Quarantined against her will, the story reveals the newfound power of health officials to protect the masses, often at the expense of personal liberties.